1996
DOI: 10.1152/ajpendo.1996.271.4.e694
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum potentiates P(i) transport stimulation induced by fluoride in osteoblast-like cells

Abstract: The effect of aluminum (AI) on inorganic phosphate (P(i)) transport stimulation induced by fluoride (F) was investigated in MC3T3-E1 osteoblast-like cells. Al potentiated the increase in P(i) transport activity induced by F in a dose- and time-dependent manner. Results obtained with deferoxamine mesylate, an Al chelator, suggest that a fluoroalumino complex is probably the active F molecule responsible for the change in P(i) transport observed in this study. The signaling pathway responsible for the stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Recent information from this laboratory indicated that in addition to its effect on cell proliferation, AlFx also enhanced Pi transport activity in MC3T3‐E1 cells 19. Analysis of the signaling mechanism responsible for this effect also suggested the involvement of a G protein and a tyr phos process 19. Therefore, the effect of PTX on changes in Pi transport activity induced by AlFx was also investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent information from this laboratory indicated that in addition to its effect on cell proliferation, AlFx also enhanced Pi transport activity in MC3T3‐E1 cells 19. Analysis of the signaling mechanism responsible for this effect also suggested the involvement of a G protein and a tyr phos process 19. Therefore, the effect of PTX on changes in Pi transport activity induced by AlFx was also investigated.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that this subtype of heterotrimeric proteins is involved in cell proliferation induced by fluoride. In addition to its effect on cell replication, pertussis toxin also reduced the stimulation in Pi transport activity induced by AlFx (Table 1) suggesting that this subtype of G proteins also regulates Pi transport activity in response to AlFx 19. Since it has been proposed that Pi transport may play a functional role in the calcification of the bone matrix,26 this observation suggests that activation of Gi or Go proteins in osteogenic cells may be important for controlling not only cell division but also the differentiation of bone‐forming cells.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, in MC3T3-E1 cells, it was reported that the PI-3-kinase pathway might also be involved in P i transport stimulation induced by PDGF, (26) whereas a tyrosine phosphorylation-dependent and PKC-independent mechanism mediates the stimulation of P i transport in response to fluoroaluminate. (39) In addition to PLC-␥, bFGF enhanced the tyrosine phosphorylation of several other proteins, including a 90-kDa protein. However, specific anti-80K-H and anti-FRS2 antibodies did not recognize this 90-kDa protein.…”
Section: Discussionmentioning
confidence: 99%
“…Even though PLC‐γ appears to be an essential regulator of P i transport stimulation induced by growth factors that act through receptor tyrosine kinases, indirect evidence have been provided to implicate additional tyrosine phosphorylation–dependent processes in the regulation of P i transport. For instance, in MC3T3‐E1 cells, it was reported that the PI‐3‐kinase pathway might also be involved in P i transport stimulation induced by PDGF, (26) whereas a tyrosine phosphorylation–dependent and PKC‐independent mechanism mediates the stimulation of P i transport in response to fluoroaluminate (39) . In addition to PLC‐γ, bFGF enhanced the tyrosine phosphorylation of several other proteins, including a 90‐kDa protein.…”
Section: Discussionmentioning
confidence: 99%
“…Desferrioxamine and Ferelax-G, two small organic compounds, have been created that bind aluminum with logarithmic stability constants of 22 and at least 22, respectively [2]. Previous research suggests that a fluoroalumino complex is probably the active fluorine 0162-0134/$ -see front matter Ó 2007 Elsevier Inc. All molecule responsible for the change in P i transport as investigated in osteoblast-like cells important in bone formation [4] as suggested by the addition of deferoxamine mesylate, an aluminum chelator that could inhibit the response. A mix of Feralex-G and ascorbate and desferrioxamine and ascorbate were found to be the best Al 3+ chelators in tissues [2].…”
Section: Introductionmentioning
confidence: 99%